INCLUSIVENESS IN EDUCATIONAL PROCESSES AS MEANS OF PROVIDING EQUAL ACCESS TO EDUCATION (Scientific journal of the Fergana State University, 2023)
In pedagogy inclusive learning is considered as means for seeking to meet the needs of all the learners, despite of their background or identity, and promoting their participation in subject matter.Inclusive learning and teaching provides equal rights to all students to learning process that respects diversity, ensures participation, removes barriers, anticipates and accommodates different learning needs and preferences, designing and implementing teaching, learning and assessment methods that enable all learners to participate meaningfully in the learning environment program and reach their full potential.The main focus of this article is inclusive education as an urgent issue of ensuring the involvement of all, regardless of the abilities of students, creating equal access to the educational process for all the students with disabilities and without. The article considers a number of legislative acts adopted regarding inclusiveness in education and provides information on the legislative acts which have been taken both at the global level - and in a single country, the acts directed to the revision of the educational process and also creating favorable learning conditions. It also discusses the professional training of a teacher and the development of educational material to ensure the quality of inclusiveness in the educational process.